Identification Of Intestinal Worms On Horses At The Cipanas Presidential Palace Using The Flotation Method - Siagian, Tetty Barunawati; Malik, Abdul; Nuriman, Trian Gustiana (Universitas Andalas, 2024)
The Cipanas Presidential Palace has local horses with sandalwood and sumbawa types that are used as riding horses and decorative horses to beautify the palace. The horses are kept by being stabled in the afternoon until morning, and being let out in the morning until evening. This maintenance method certainly carries a risk of gastrointestinal worm infection and often worm infections in horses do not cause clinical symptoms. The purpose of the study was to identify the types of gastrointestinal worms that infect horses at the Cipanas Presidential Palace. This study used fecal samples from 26 horses that were examined using the flotation method. The results of the examination showed that 24 samples were positive for strongylid worm eggs. The percentage of worm infection in horses at the Cipanas Presidential Palace was 92.3%. The findings of Strongylid worm eggs are oval with thin walls and have morula like grapes. Adult worms that have Strongylid worm eggs are Strongylus vulgaris. The cause of horses being infected with worms is due to being let out too early, giving wet grass that is not wilted, and storing wet grass in a damp warehouse. Based on the research above, it was concluded that local horses at the Cipanas Presidential Palace were infected with Strongylus vulgaris worms.